'Feeding our families; that's what we have been doing for centuries': Inuit women's sharing practices and strategies. Issue 4 (April 2019) - Quintal-Marineau, Magalie
Abstract : Inuit families in the Canadian North use a mixed food system, combining country and store-bought foods. However, the Inuit food system is more complex than the combination of market and country food; it encompasses a whole set of sociocultural relations. Using a sociocultural and gender perspective, this paper explores contemporary food-sharing practices focusing on access to market foods, the flow and the specific ways they are shared in the Baffin region, Nunavut. While results show that store foods are shared with extended family members and within the community, the sharing of market foods is not regulated through similar mechanisms as country foods, and is not fully integrated in the Inuit traditional resource sharing system (ningiqtuq). Also, women are shown to play a key role in accessing, transforming and sharing southern foods. Through their wages, women are reproducing the normative sharing behaviour that underpins subsistence as a social economy, albeit through a novel medium. The paper suggests that modern Inuit food practice is articulated around a new gender dynamic that challenges traditional social configuration.